2022
DOI: 10.1530/eje-22-0375
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes and all-cause mortality in primary aldosteronism after adrenalectomy or mineralocorticoid receptor antagonist treatment: a meta-analysis

Abstract: Background: In patients with primary aldosteronism (PA), long-term cardiovascular and mortality outcomes after adrenalectomy versus mineralocorticoid receptor antagonist (MRA) have not been compared yet. We aim to compare the clinical outcomes of these patients after treatment. Design and Methods: A systematic review and meta-analysis was conducted by searching PubMed, Cochrane library, and Embase from no start date restriction to Dec 18, 2021. Our composite primary outcomes were long-term all-cause mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…Adrenalectomy, when feasible, has shown, over the year, its superiority over medical treatment for the prevention of major cardiovascular events, all-cause mortality, and improvement of quality of life. 22,23 Most predictors of clinical success are only risk factors of essential hypertension, probably concomitant with primary aldosteronism. 24 Biological success (ie, a normal postsurgery ARR) should be the most regarded parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenalectomy, when feasible, has shown, over the year, its superiority over medical treatment for the prevention of major cardiovascular events, all-cause mortality, and improvement of quality of life. 22,23 Most predictors of clinical success are only risk factors of essential hypertension, probably concomitant with primary aldosteronism. 24 Biological success (ie, a normal postsurgery ARR) should be the most regarded parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown beneficial effects on cardiovascular comorbidities in patients with PA treated with unilateral adrenalectomy. 13,15,16 Furthermore, previous studies have indicated that all-cause mortality in surgically treated patients with PA is not increased and may in fact be lower than the mortality risk in patients with essential hypertension or in patients receiving medical treatment for PA. 15,16,26,27 These results are in line with our study, showing that mortality in patients treated with unilateral adrenalectomy is similar to age- and sex-matched controls. However, comparing mortality in patients receiving medical and surgical treatment may be misleading, given that medically treated patients are older and more often have clinically manifest cardiovascular diseases when PA is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the mean follow-up time in the largest study, which included 2448 patients (ie, 81% of the patients that were included in the meta-analysis) was 4.3 years compared with 8 years in our study. 16 Thus, reliable data on mortality during long-term follow-up have not been available from previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not helpful to predict the cure rate or long-term prognosis before surgery. Although adrenalectomy currently is preferred for patients with PA concerning the risk of all-cause mortality and major adverse cardiovascular events compared to medical treatment ( 129 ), predicting the types of mutations with simple and safe methods before surgery would possibly allow physicians to make a comprehensive treatment strategy for patients. Future studies are needed to explore the most appropriate diagnostic methods.…”
Section: Kcnj5 Somatic Mutationsmentioning
confidence: 99%